SMART CAR PARKING SYSTEM FOR VEHICLES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In day to day life theres massive drawback of parking of cars in metro cities attributable to lack of parking areas. So now a days we are constructing new system to solve this problem named as multilevel automatic parking system for vehicles Robotic automotive parking system. That the project work is to develop a automotive parking system that permits 6 to 26 cars inside an area of 32.17 sq.m with security of fingerprint ID for licensed entry solely. This model is very helpful for development in numerous areas like automation i.e. PLC micro-controllers and automation.